Modeling Software Project Management with Norms and Reputation - Baía, Davy; Cirilo, Elder; Lucena, Carlos (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC); 2013: Anais do VII Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações, 2013)
The development of software projects and its results have received substantial attention from academia in the past years, mostly due to the fact that projects frequently do not achieve their expected results. Recent researches has highlighted how crucial the project manager efficiency is, in terms of project management since its activities have a straight impact in improving the success of such projects. Accomplishing such management activities in an efficient way, however, has been a challenge for most project managers. Through this paper, we propose the creation of a set of agents by applying norms and reputation concept in order to assist the project manager. We use norms to support the manager in the process of knowledge composition whereas reputation gives a better overview of each human resources in the project. Furthermore, to evaluate the proposed set of agents, we conducted exploratory case study, providing a detailed description of how the set of agents acted in a project simulation.